The Urgency of Students' Academic Resilience at School - Zulfikar Zulfikar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The many demands and academic pressures at school and at home trigger the emergence of stressand depression in students. To deal with it, academic resilience is needed, namely the ability of students toeffectively overcome difficulties to rise from academic failure and be able to return to achieving success in adepressed state by not giving up facing it. But on the other hand, students do not yet fully have academicresilience which can be seen in their behavior in dealing with academic problems. Without academicresilience, students will experience failure that has an impact on their future. Academic resilience is obtainedthrough a learning process and experience from the environment. The school environment has an importantrole in developing academic resilience. This is inseparable from the role of BK teachers in developing it.Counseling teachers can make various efforts such as building or strengthening student relationships withtheir social environment. Then provide various forms of guidance that can be independent and fosterstudent confidence and self-confidence. All of this needs to be done by integrating it into every guidance andcounseling service in schools